The influence a community nursing course has on the selected knowledge of nurses with regard to rules for measuring blood pressure - Grabowska, Hanna; Grabowski, Władysław; Grzegorczyk, Michał; Gaworska-Krzemińska, Aleksandra; Świetlik, Dariusz; Narkiewicz, Krzysztof (Nursing Problems / Problemy Pielęgniarstwa, 2009)
Introduction. High blood pressure has become an serious cause of disease and death in the world despite the fact that it is one of the easiest symptoms to recognize. This is why correctly measuring blood pressure remains a key professional skill for the modern nurse. Aim of research. To show the influence a community nursing course has on the degree of knowledge about selected rules recommended while measuring blood pressure in an ambulatory or GP surgeries. Materials and methods. This research is based on 186 people (average age 41.7; average work experience 20 years) of whom 73 work as community nurses having finished a community nursing course, 47 work in GP surgeries without a course, and 66 work in other environments having finished a community nursing course. The research was carried out in 2007-2008 using diagnostic survey questionnaires. The research tool was our own questionnaire. The statistical analysis was carried out using the STATISTICA programme, version 8.0, a p value £ 0.05 was regarded as significant. Results. Those questioned showed a high level of knowledge about the influence of factors which should be reduced before measuring blood pressure. Half of those questioned correctly identified the recommended speed of deflation of air from the cuff, while 34.4% knew where to correctly place the lower edge of the cuff. The influence of the width of the cuff on blood pressure values was correctly given by just 12.9% of people. The results show a statistically significant difference in correct answers depending on a finished community nursing course (p = 0.0395). Conclusion. Those questioned showed an average level of knowledge about the rules recommended while measuring blood pressure - it was higher in the group of people who had taken the community nursing course. It is vital to have frequent, regular and up-to-date training for nurses in order to follow the rules for measuring blood pressure.